The fresh water company: Private projects for drinking water supply systems in Peru and Mexico, 1846-1856 - Birrichaga Gardida, Diana (2006)
In the mid-nineteenth century and in different countries of America, an urban policy emerged aimed at modifying the old colonial layout of cities, through the construction of public works. This modernization process included the transformation of the hydraulic system; City councils, state governments, companies and individuals began to introduce technical improvements to the drinking water distribution system by installing a network hydraulic system.